MORPHOLOGY OF MULBERRY HYBRIDS IN PURWOBINANGUN YOGYAKARTA - Sugeng Pudjiono; Sendy Septina (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
There are many genetic which effect this fenotipic character, such as hybrid. In increasing of mulberry hybrids, it is needed to identify the characteristic of those hybrids. The purpose of this research is to identify morphological characteristics among mulberry hybrids. Observation was done to nine hybrids and five female, four male of mulberry. There are some similarities of morphological characterictics i.e. : performance shcrub, pennivervis leaf, texture of leaf bottom smooth, phyllotaxis 2/5, leaf type singular, stem type woody, stem size cylinder, growth erectus, branch type monopodial, growth of branch patens, root type radix primaria, shoot position axillaris and it has stypulla. Differences of the characteristic on mulberry can be seen at leaf type shape, leaf bottom shape, leaf side, texture of leaf surface, leaf color, leaf index length/width, average of petiole length, lentisel density on surface stem, stem color, stem diameter, and average of internodal distance.